In Search of the Third Code: An Investigation of Norms in Literary Translation - Øverås, Linn (Meta, 1998)
AbstractThis paper is an investigation of explicitation in translational English and translational Norwegian. The study is aimed at unveiling the specificity of the language of translation regardless of the contrastive differences existing between the two languages. The ultimate objective, however, goes beyond the mere linguistic investigation in as far as it attempts to reach conclusions about the literary translational norms prevaling in the target communities it has studied.